IPv4 to IPv6 Transition Strategies for Enterprise Networks in Developing Countries - Sansa-Otim, Julianne S.; Mile, Anthony (Springer, 2012)
Internet Protocol version 4 (IPv4) addresses have been reported to be nearing exhaustion and the next generation Internet Protocol version 6 (IPv6) is gradually being deployed in the Internet. IPv6 provides a much larger address space, better address design and greater security, among other benefits. IPv6 deployment requires thorough and careful preparation to minimize network disruption and ensure that the benefits of IPv6 are obtained. The migration from IPv4 to IPv6 cannot be achieved in a short period thus the two protocols will co-exist for some time. Unfortunately, these two protocols are incompatible; hence for them to co-exist, various IPv4-to-IPv6 transition mechanisms have been developed. In this paper, we analyse the different site-to-site tunneling mechanisms through a theoretical and experimental evaluation to study their appropriateness in IPv6 deployment for enterprise networks in developing countries. Using five performance metrics, namely: endto- end delay, jitter, throughput, packet loss and CPU utilization, our experimental results indicate that Configured Tunneling performs better than the other tunneling mechanisms. This study is of importance to those enterprise networks which want to implement IPv6 and are concerned about which transition mechanisms to embrace depending on the performance requirements.
Keywords: IPv4-IPv6 translation; GRE tunneling; 6to4 tunneling; Configured tunneling